2007
DOI: 10.1111/j.1439-0531.2006.00696.x
|View full text |Cite
|
Sign up to set email alerts
|

Sperm distribution in the reproductive tract of sows after intrauterine insemination

Abstract: The purpose of the present study was to compare the number of spermatozoa obtained from different parts of the oviducts and the uterine horns of sows after intrauterine insemination (IUI) and conventional artificial insemination (AI), 24 h after insemination. Twelve crossbred (Landrace x Yorkshire) multiparous sows were used in the experiment. The sows were examined for standing oestrus using a back pressure test and were examined every 4 h after standing oestrus by real-time B-mode ultrasonography to estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
61
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 21 publications
7
61
0
1
Order By: Relevance
“…The low amount of neutrophils and macrophages indicates that the function of the non-specific immune system or phagocytosis is limited in the sperm reservoir as suggested in the previous study by Rodriguez-Martinez et al [13]. In general, the number of sperm used for IUI and DIUI was 3 and 20 times less than for CAI [17,20]. Our previous study has also demonstrated that the number of sperm in the crypt of the sperm reservoir (UTJ and caudal isthmus) in the DIUI groups was also lower than that with CAI [21].…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…The low amount of neutrophils and macrophages indicates that the function of the non-specific immune system or phagocytosis is limited in the sperm reservoir as suggested in the previous study by Rodriguez-Martinez et al [13]. In general, the number of sperm used for IUI and DIUI was 3 and 20 times less than for CAI [17,20]. Our previous study has also demonstrated that the number of sperm in the crypt of the sperm reservoir (UTJ and caudal isthmus) in the DIUI groups was also lower than that with CAI [21].…”
Section: Discussionmentioning
confidence: 65%
“…In the present study, the numbers of inflammatory cells (neutrophils and plasma cells) in some part, especially in the UTJ, of the oviduct were higher in the CAI than the DIUI groups and also tended to be higher than in the IUI groups. The reason might be due to the number of spermatozoa depositing in the UTJ and oviduct of sows after DIUI with a reduced number of spermatozoa was significantly lower than that after CAI [17]. Since either the volume of semen or the total number of spermatozoa used for DIUI were 20 times less than CAI, some seminal plasma proteins that can induce PMN cells might be low.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations